Micropropagation of four varieties of cassava (manihot sculenta crantz) with export and industrial potential in the Dominican Republic - Peralta Corona, Héctor Rafael; Mejía Brea Rosario, Julio Bolívar; Jesús, Carmen María de; Díaz Román, Manuel; Martínez Tejada, Daniel; Escobar Pérez, Roosevelt Humberto (IJAEB Publication, 2022)
Cassava (Manihot sculenta Crantz) has been a source of carbohydrates for low-income sectors of the population worldwide. Cassava is implicit in food security and sovereignty. The limitations of this crop to produce it are the lack of healthy material for planting and low yield levels. Cuttings from conventional cassava plantings are infested with pathogens and these are difficult to eliminate with existing procedures. This affects growth and yield. The massive in vitro multiplication of cassava contributes to the food security of Dominicans and the recovery of export markets. In vitro cassava plants were obtained to supply producers with high quality and yield varieties. In addition to being used in agro-industry, strengthening exports and satisfying the demand for material, it is important that the extraction of healthy material exceeds the traditional supply. For this reason, in vitro culture techniques are playing an important role in the maintenance of collections, sanitation and rejuvenation of the material whose yields are tripled when using in vitro cassava plants.